Physiological value of intestinal microflora - S. Yu. Kuchumova; Ye. A. Poluektova; A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss basic functions of microorganisms colonizing human gastro-intestinal tract (GIT), methods of diagnostics of their qualitative and quantitative composition, state at which imbalance of intestinal microflora is possible and treatment options.Original positions. The human body is inhabited by approximately 500 species of microorganisms. Microflora of gastro-intestinal tract is most representative both by qualitative and quantitative composition. The density of bacteria steadily grows from quite mobile small intestine to less mobile large intestine. Microbiocenoses are characterized by complex hierarchical structure, various interspecies attitudes and carry out set of functions beyond GIT, i.e. immunomodulating, synthetic, absorptive, detoxifying, anticancerogenic, alimentiry, motor and protective. Now there are essentially two various approaches for assessment of intestinal microflora – direct and indirect. Direct methods are based on revealing of living culture. They include culture of smallintestinal aspirate or biopsy specimen. Indirect methods, like various breath tests are based on revealing of bacteria metabolism products in the exhaled air. In the last years in clinical practice chemical methods, in particular gas chromatography (GC) in combination to mass spectrometry (GC-MS) are actively developed, the method of fluorescent DNA hybridization in situ (FISH) is applied, polymerase chain reaction (PCR-diagnostics) became quite widespread method of microorganisms assessment. The range of diseases accompanying by imbalance of intestinal microflora, is outlined quite presumably. Probiotics can be applied for treatment of disordered intestinal microflora, defoamers — as symptomatic treatment. However the theoretical base explaining action of these agents, remains poor, that requires the further studies in this area.Conclusion. Intestinal microflora is integral part of each individual. Further studying of its functions, the states interfering qualitative and quantitative composition of microorganisms, colonizing human gastrointestinal tract, as well as the mechanism of action of probiotics and drugs of symptomatic action (defoamers) is necessary.